INSTITUTIONAL SUPPORT FROM CREDIT UNION OF TORAJA CHURCH SYNOD FOR CONGREGATION ECONOMIC EMPOWERMENT - Donald Samuel Slamet Santosa,; I Wayan Ruspendi Junaedi,; I Wayan Damayana,; Dermawan Waruwu,; I Made Sumartana, (International Journal of Social Science, 2022)
The article was aimed to analyze the institutional support given by the Credit Union of Toraja Church Synod for congregation economic empowerment and then to construct the model of this institutional support. Research typology in this article was research and development. The development intended by this research was referred to Developmental Model 4D (Define, Design, Develop, and Dissemination). The outputs of this research were the factual model outlining institutional support for congregation economic empowerment, the hypothetical model expected to improve factual model, and the validated final model. Research approach involved quantitative and qualitative approaches. The results of research showed that the Credit Union of Toraja Church Synod had offered institutional supports including credit facility to be accessed by the congregation. The new model illustrated the participation of the congregation in the decision making process of the Credit Union and also the training and counseling services provided by the Credit Union for the congregation in matters of taking loan for business development. The new model was proved to be effective in empowering the congregation economic.